How I Diagnose Anaplastic Large Cell Lymphoma. Issue 4 (4th March 2021) - Amador, Catalina; Feldman, Andrew L
Abstract: Objectives: This review describes our approach to the diagnosis of all 4 anaplastic large cell lymphoma (ALCL) entities. Methods: ALCLs are a group of CD30-positive mature T-cell lymphomas with similar morphologic and phenotypic characteristics but variable clinical and genetic features. They include systemic ALK-positive ALCL, systemic ALK-negative ALCL, primary cutaneous ALCL, and the recently described provisional entity breast implant–associated ALCL. Results: In cases with classic features, the diagnosis of ALCL is often straightforward. However, variant histology, the importance of clinical history, and multiple antigenic aberrancies all present challenges to accurate diagnosis and subclassification. Conclusions: A systematic approach to the diagnosis of ALCL and awareness of potential mimics are critical to avoid misdiagnosis. It is also crucial to correctly identify localized forms of ALCL to avoid classification as systemic ALCL and subsequent overtreatment.